Investigation of the Prevalence of Strongyloides Stercoralis and other Intestinal Parasites in Patients with Psychiatric Disorders Admitted to Sina Hospital in Hamadan in 2021 - GH Valizadeh; M Fallah; M Motavalli haghi; A Keshavarzi; M Bakhtiari (Armaghane Danesh Bimonthly Journal)
Background & aim: Infection with Strongyloides stercoralis is endemic worldwide and its prevalence is higher in warm and humid regions and poor countries. The frequency of infection is higher in people with immunodeficiency and in collective centers, including centers for patients with psychiatric disorders and prisoners, where hygiene principles are not fully observed, and dangerous parasitic infections such as Strongyloides stercoralis have been frequently reported. As a result, the present study aimed to determine and investigate the prevalence of Strongyloides stercoralis and other intestinal parasites in patients with psychiatric disorders hospitalized in Sina Hospital in Hamadan.